Van der Waals engineering for quantum-entangled photon generation - Kallioniemi, Leevi (2025)
Van der Waals engineering serves as a powerful tool to tailor material properties and design excitonic devices. Here we report quantum-entangled photon pair generation through van der Waals engineering with two-dimensional materials. We align two van der Waals thin layers perpendicular to each other, yielding polarization-entangled photon pairs through the interference of biphoton emission in the two flakes. The polarization-entangled state is measured with a fidelity up to 86 ± 0.7%. The compatibility of van der Waals engineering with on-chip photonics opens new possibilities for entangled photon source integration at the subwavelength scale.